Design and Construction of Cooperative Information System - Hedi Pandowo; Dian Kusumaningrum; Hamim Tohari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cooperative is a business that conducts administrative transactions. Computerization in the field of administration is important to support the smooth running of all transactions quickly, precisely, and accurately. In order to meet these needs, an integrated system is needed, and is able to follow changes in business processes that occur. Objective: to produce a desktop-based application program that can be used to facilitate cooperative management using the ProtoTyping method. Method: Research and Development research was chosen to find or create new products that have advantages in terms of effectiveness, efficiency, and productivity. The research stages start from formulating the problem, analyzing the results and drawing conclusions. This research was conducted in April 2025. The research location was at Koperasi Mandiri Karangrejo Magetan. The approach used is using the Prototyping model. Data collection techniques include interviews, observations and questionnaires. Analysis tests are developed on aspects of functional suitability, reliability aspects with the help of software called Web Application Load, Stress and Performance Testing (WAPT), and usability aspects. Results: a blueprint is produced which is used as a reference in the development of the cooperative information system at the Mandiri Cooperative. Using the Requirements gathering and analysis, Quick design, build prototype, User evaluation, refining prototype, Implement product and maintain design methods, it produces a structured design as the basis for system implementation. The architecture designed is a cooperative information system integrated with computer network technology. Conclusion: the study has compiled a cooperative information system design at the Mandiri Karangrejo Magetan Cooperative which can be accepted with satisfactory assessment results.